2022
DOI: 10.1152/ajpendo.00365.2021
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular flux analyses reveal differences in mitochondrial PBMC metabolism between high-fit and low-fit females

Abstract: Analyzing metabolism of peripheral blood mononuclear cells (PBMCs) can possibly serve as a cellular metabolic read-out for lifestyle factors and lifestyle interventions. However, the impact of PBMC composition on PBMC metabolism is not yet clear, neither is the differential impact of a longer-term lifestyle factor versus a short-term lifestyle intervention. We investigated the effect of aerobic fitness level and a recent exercise bout on PBMC metabolism in females. PBMCs from 31 young female adults divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…All 102 biomarkers were analysed in samples from a well-characterised study [ 21 , 22 , 23 ] of healthy females. This study population represents high-fit (V̇O 2 peak ≥ 47 mL/kg/min, N = 15) and low-fit (V̇O 2 peak ≤ 37 mL/kg/min, N = 15) females ( Table 1 ), which was supported by a significantly higher skeletal muscle mitochondrial capacity for ATP generation [ 21 ] and a better mitochondrial function, including higher basal and uncoupled oxygen consumption rate, in peripheral blood mononuclear cells (PBMCs) [ 22 ] in the high-fit compared to the low-fit females.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 102 biomarkers were analysed in samples from a well-characterised study [ 21 , 22 , 23 ] of healthy females. This study population represents high-fit (V̇O 2 peak ≥ 47 mL/kg/min, N = 15) and low-fit (V̇O 2 peak ≤ 37 mL/kg/min, N = 15) females ( Table 1 ), which was supported by a significantly higher skeletal muscle mitochondrial capacity for ATP generation [ 21 ] and a better mitochondrial function, including higher basal and uncoupled oxygen consumption rate, in peripheral blood mononuclear cells (PBMCs) [ 22 ] in the high-fit compared to the low-fit females.…”
Section: Resultsmentioning
confidence: 99%
“…The original objectives of the study were to investigate whether differences exist in vitamin B2 status, in muscle mitochondrial capacity, and in circulating cellular and molecular parameters between high aerobically fit (high-fit) and low aerobically fit (low-fit) females with a validated difference in V̇O 2 peak, and after a recent bout of exercise. Previously, we found a significant difference in skeletal muscle mitochondrial oxygen consumption rate [ 21 ] and mitochondrial function in white blood cells [ 22 ] between the high-fit and low-fit females in our healthy study population. Circulating biomarker and metabolic parameter analysis in this study will now show whether single biomarkers, functional biomarkers, metabolic parameter categories, total biomarkers, and metabolic parameter profiles differ between high-fit and low-fit females, i.e., whether the biomarkers and metabolic parameter, including those that discriminate between health and disease, already differ in healthy individuals with potentially a different long term disease risk, in the basal state and after a recent bout of exercise.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Particularly, the interest in the fraction of peripheral blood mononuclear cells (PBMC) as a biological material for searching for biomarkers related to different diseases, e.g., obesity has grown in the last years. [16][17][18][19] Apart from their role in immunology, PBMC express a significant proportion, around 80%, of the genes encoded by the human genome and act as "sentinel" cells capable of reflecting gene expression profiles of internal tissues. [20] In fact, we have previously shown that gene expression of selected key lipid metabolism genes in human PBMC is affected by OW-OB in the same way as in crucial energy homeostatic tissues.…”
Section: Introductionmentioning
confidence: 99%